2019
DOI: 10.1002/anie.201900723
|View full text |Cite
|
Sign up to set email alerts
|

Minimizing the Entropy Penalty for Ligand Binding: Lessons from the Molecular Recognition of the Histo Blood‐Group Antigens by Human Galectin‐3

Abstract: Ligand conformational entropy plays an important role in carbohydrate recognition events. Glycans are characterized by intrinsic flexibility around the glycosidic linkages, thus in most cases, loss of conformational entropy of the sugar upon complex formation strongly affects the entropy of the binding process. By employing a multidisciplinary approach combining structural, conformational, binding energy, and kinetic information, we investigated the role of conformational entropy in the recognition of the hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
77
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 63 publications
(89 citation statements)
references
References 37 publications
(33 reference statements)
8
77
2
2
Order By: Relevance
“…The measurements of binding constants obtained using MST, TFS and ITC and even molecular docking are consistent with the Au 3+ TPPS-Gal3 FL interaction of low micromolar affinity. The affinity of Au 3+ TPPS for Gal3 FL is higher than for LacNAc with one binding site but lower than for asialofetuin (K D = 720 nM) with nine LacNAc epitopes [57] and is the same as for blood group type II [45]. Similar to the interaction with oligosaccharides and the asialofetuin glycoprotein, the binding of Au 3+ TPPS is enthalpically driven, however the entropic contribution to binding is also positive.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The measurements of binding constants obtained using MST, TFS and ITC and even molecular docking are consistent with the Au 3+ TPPS-Gal3 FL interaction of low micromolar affinity. The affinity of Au 3+ TPPS for Gal3 FL is higher than for LacNAc with one binding site but lower than for asialofetuin (K D = 720 nM) with nine LacNAc epitopes [57] and is the same as for blood group type II [45]. Similar to the interaction with oligosaccharides and the asialofetuin glycoprotein, the binding of Au 3+ TPPS is enthalpically driven, however the entropic contribution to binding is also positive.…”
Section: Discussionmentioning
confidence: 92%
“…However, H(2)TPPS binds by intruding, overlapping or allosterically hindering the carbohydrate-binding sites of concanavalin A, peanut agglutininin and jacalin, respectively, therefore porphyrin binding might negatively interfere with the highly selective cancer-antigen targeting function of the plant lectins [38]. An earlier study demonstrated that zinc tetrasulfonatophenylporphyrin (Zn 2+ TTPS) binds Gal3 with high affinity (K d = 0.18 µM) [42], largely surpassing N-acetyllactosamine, that is generally considered to be a specific binder of Gal3, with reported affinities K d = 25 µM [43], 28 µM [44], 112 µM [45] and 118 µM [46]. Most importantly, lactose did not inhibit Zn 2+ TTPS binding [42], suggesting that carbohydrate binding might be compatible with the binding of the porphyrin photosensitizers.…”
Section: Introductionmentioning
confidence: 99%
“…However,g iven their intrinsic flexibility,e specially for Ib, both molecules could be accommodated to interactw ith the monoclonal binding pockets without am ajor entropyp enalty. [31]…”
Section: Conformational Analysismentioning
confidence: 99%
“…However, no common strategy exists for a rational selection of mutations for design of high‐affinity carbohydrate‐binding proteins. The inherent flexibility of the glycan ligand often has major impact on the energetics of protein–carbohydrate complex formation . Flexibility in glycans can be functional to sample a large conformational space for binding sites and provide higher avidity in multivalent settings .…”
Section: Introductionmentioning
confidence: 99%